An enquiry into the conduct of our domestick affairs, from the year 1721, to the present time, in which the case of our national debts, the sinking fund, and all extraordinary grants of money, are particularly consider'd, being a sequel to politicks on both sides (Haines, 1734)
Author: William Pulteney (Earl of Bath).